Model-T2 - Development of a low-cost sustainable vehicle: Collaboration models in concept car design - Rolfe, B.; Hanafin, S.; de Souza, T.; Datta, Sambit (Curtin Sarawak, 2011)
One of the largest problems facing the world today is the rise of Indian and Chinese car owners, and their lack of access to low cost sustainable vehicles. China and India have very low vehicle ownership per capita, however, this is quickly changing. Both their Governments are heavily investing in sustainable vehicle technologies to reduce green house gas emissions, and reduce each countries dependency on oil. This paper will outline a new sustainable vehicle that can compete with the low cost vehicles currently avaliable. This novel concept was the inspiration from a cross-functional team comprising engineers and designers working on a low-cost sustainable concept car project, the Model T2. The main features of this concept are: world first $7000 sustainable vehicle, an incredible light weight structure, and a novel steering mechanism for maximum maneuverability.